Productivity growth and efficiency dynamics of Korean structural transformation - Jeong, Hyeok (World Bank Group, Development Economics, Development Research Group, 2020)
This paper documents the sources of the Republic of Korea's economic growth, as well as the associated productivity growth and efficiency dynamics during its process of structural transformation from 1970 to 2016. The analysis includes land as a separate production factor to sort out the significant effect of changes in intersectoral land allocation, which makes significant differences in measuring the magnitudes and directions of change in sectoral total factor productivity (TFP). Input-based growth and structural changes contributed to the early take-off stage of growth in the 1970s. However, in the following three decades, the source of growth switched to productivity improvements, mainly engineered by the industry sector. This was the reason behind the country's sustained growth and escape from the
10.1596/1813-9450-9285
Keywords: Graue Literatur; Structural Transformation; Measurement of TFP and Wedges; Productivity Growth; Efficiency Dynamics; Korean Economy; Sustainable Development